2019
DOI: 10.1007/s13205-019-1592-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects on cholinesterase of blood of Oreochromis mossambicus by copper

Abstract: The present study is aimed to evaluate the effects of sub-acute toxicity testing of copper sulphate (CuSO 4), on behavioural, histological and biochemical changes of the Oreochromis mossambicus (black tilapia) blood tissues. The effects were assessed according to the previous results on sub-acute toxicity test after exposing fish to several concentrations (0.0, 2.5, 5.0, and 10.0 mg/L). The observations of scanning electron microscope, and transmission electron microscope studies revealed severe histopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Samajdar et al, 2015), and that we find CPF to be strongly toxifying to clownfish blood cells or to their precursors (downregulation of all haemoglobin genes), may suggest that it is blood populations that are the ones damaged the most. In fact, acetylcholinesterase is an important membrane component of red blood cells and erythropoietic cells (Lawson and Barr, 1987;Basirun et al, 2019) and, at least in humans, has been found to be a more sensitive readout of organophosphate exposure than other isoforms (Chen et al, 1999).…”
Section: Systemic Effects Of Cpf On Clownfish Larvaementioning
confidence: 99%
“…Samajdar et al, 2015), and that we find CPF to be strongly toxifying to clownfish blood cells or to their precursors (downregulation of all haemoglobin genes), may suggest that it is blood populations that are the ones damaged the most. In fact, acetylcholinesterase is an important membrane component of red blood cells and erythropoietic cells (Lawson and Barr, 1987;Basirun et al, 2019) and, at least in humans, has been found to be a more sensitive readout of organophosphate exposure than other isoforms (Chen et al, 1999).…”
Section: Systemic Effects Of Cpf On Clownfish Larvaementioning
confidence: 99%